Biosynthesized Zinc Nanoparticles Using Melia azedarach: Characterization and Antimicrobial Activity as an Alternative to Antibiotic Growth Promoters in Broilers - Wasir Ibrahim; Nurhayati; Mairizal (Animal Husbandry Department, The Faculty of Agriculture, Universitas Syiah Kuala, 2026)
The use of antibiotic growth promoters (AGPs) in poultry feed has been shown to improve production efficiency; however, their use has been restricted because of concerns regarding antimicrobial resistance. This study aimed to evaluate the potential of biosynthesized zinc nanoparticles (ZnNPs) using Mindi leaf extract (Melia azedarach) through nanoparticle characterization and antimicrobial activity assessment. ZnNPs were synthesized by mixing 70 mL of a 1 mM zinc nitrate hexahydrate solution with 30 mL of mindi leaf extract. Characterization using a Particle Size Analyzer showed an average particle size of 380.8 nm, polydispersity index (PDI) of 0.572, intercept value of 0.927, and zeta potential of −23.7 mV, indicating moderate dispersion stability. Antimicrobial activity was evaluated against Escherichia coli, Salmonella typhimurium, and Lactobacillus sp. using the disk diffusion method. ZnNPs at a concentration of 1000 ppm produced inhibition zone diameters of 18.47 mm and 17.23 mm against E. coli and S. typhimurium, respectively (P<0.01). These inhibition zones approached those of tetracycline (45 ppm) under the tested conditions, whereas no inhibitory effect was observed against Lactobacillus sp. The observed antibacterial activity may be associated with nanoparticle–cell membrane interactions, Zn²⁺ ion release, and the generation of reactive oxygen species (ROS), as reported previously. These findings indicate that the biosynthesized ZnNPs exhibit selective antibacterial activity against pathogenic bacteria. However, further in vivo studies are required to confirm their efficacy and safety before considering their application as alternatives to AGPs in poultry production.